GERAKAN LITERASI REMAJA MELALUI SOSIALISASI DAN BEDAH NOVEL ANAK RANTAU DI SMP NEGERI 10 MEDAN - Lestari Dara Cinta Utami Ginting; Lila Pelita Hati; Intan Erwani; Vivi Adryani Nasution (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The literacy culture among teenagers still faces serious challenges, indicated by the declining interest in reading at schools. This community service activity aims to increase students’ reading interest through literacy socialization and a novel review of Anak Rantau by Ahmad Fuadi. The program was held on August 4, 2025 at SMP Negeri 10 Medan, involving 40 students accompanied by teachers and supported by Taman Baca Spirit Medan. The methods used were interactive lectures, discussions, quizzes, and literary analysis. Evaluation was conducted by distributing 34 questionnaires to participants. The results showed that 88% of students felt more motivated to read, 85% considered the material easy to understand, 82% found the novel relevant to teenage life, 78% were active in discussions, and 92% stated that the program was useful for school literacy programs. In conclusion, literature-based literacy programs are effective in fostering reading motivation while instilling cultural values in junior high school students.